Discussion of "assessment of the use of the vapour equilibrium technique in controlled-suction tests." - Leong, Eng Choon (2011)
The authors have highlighted the possible pitfalls of the vapour equilibrium technique in controlled-suction tests using a numerical approach. Most notable is their conclusion that forcing humid air through the sample can hasten the equilibrium condition, but may result in a suction value at equilibrium different from the intended suction.